THE EFFECTIVENESS OF THE FLOBLE LEARNING MODEL ASSISTED BY LMS EDUKATI ON CRITICAL THINKING ABILITIES IN ECONOMICS - Nihayatul Fadlillah; Muhammad Khafid; Nina Oktarina (Universitas Negeri Semarang, 2026)
Students' critical thinking skills have not yet reached an optimal level. The 2022 Programme for International Student Assessment (PISA) results indicate Indonesia's lowest performance since its first participation in 2000. This study aims to examine the effectiveness of the integrated Flipped Classroom and Problem-Based Learning (FLOBLE) model, supported by the Edukati Learning Management System (LMS), in improving students' critical thinking skills in economics. This study employed a quasi-experimental method with a non-equivalent control group design. The sample consisted of Class X-5 as the experimental group and Class X-4 as the control group at SMA Negeri 16 Semarang during the 2025/2026 academic year. Primary data were collected through pretests and posttests and analyzed using an independent-samples t-test, normalized gain (N-gain), and effect size analysis. The results show that the FLOBLE model effectively improves students' critical thinking skills in economics. The experimental group achieved an N-gain score of 71.96% (moderately effective), while the control group obtained 53.86% (less effective). The effect size value of 0.819 indicates a large effect. These findings demonstrate that the FLOBLE model is more effective than Problem-Based Learning (PBL) and provides an effective alternative for enhancing students' critical thinking skills in economics.